Antidiabetic Potential Screening of Ulin Fruit Extract (Eusideroxylon zwageri) Against Streptozotocin-Induced Diabetic Rats - Muhammad Rizani Faisal; Nada Widiasmira Amanda Oktia; Diana Aulia Mursidah; Dede Mahdiyah; Bayu Hari Mukti (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Empirical evidence of complementary medicine from one community in Kalimantan often uses Ulin fruit (Eusideroxylon zwageri) for medical therapy or as herbal drinks by people with diabetes mellitus. This research aims to identify the antidiabetic compound of Ulin fruit extract against Streptozotocin (STZ) induced diabetic rats. Extraction was performed by maceration method using 96% ethanol, phytochemical test of extracts, extract toxicity test on mice (50 mg/BW to 200 mg/BW), test antidiabetic extract in diabetic rats induced by STZ as much as 70 mg/kgBW with each extract dose of 150, 300, and 600 mg given for 14 days, positive control is Glibenclamide 0.25 mg/kg/day, and the negative control is CMC 1%. Phytochemical test results showed that the extract of Ulin contains alkaloids, tannins, flavonoids, phenolics, terpenoids, and steroids. Ulin fruit extract was not toxic to rats at 50, 150, and 200 mg for three days. Based on the Mann-Whitney test, there was an effect of giving the extract on changes in the average body weight and body temperature of rats during three days of administration (p = 0.000). The results showed novelty that the extract of Ulin fruit affected reducing blood glucose levels in diabetic rats during 14 days of administration (p=0.000).Keywords: Antidiabetic, Eusideroxylon zwageri, flavonoids, streprozotocin, diabetic rats